MON-500 A Case of Tumor-Induced Osteomalacia Caused by Metastatic Prostate Cancer - Rahman, Wedad (J Endocr Soc, 2019)
Background: Tumor-induced osteomalacia (TIO) is a rare paraneoplastic syndrome characterized by severe hypophosphatemia due to renal phosphate wasting. An overproduction of the phosphatonin fibroblast growth factor 23 (FGF-23) has been implicated in TIO pathogenesis. FGF-23 increases renal phosphate excretion by reducing the expression of sodium-dependent phosphate co-transporters NPT2a and NTP2c in the proximal tubules. TIO is most commonly associated with mesenchymal tumors. Epithelial tumors are estimated to account for only 5% of reported cases of TIO. Here we report a rare case of TIO associated with castration resistant metastatic prostate cancer. Clinical Case: A 59 year old male with high grade castration-resistant metastatic prostate adenocarcinoma presented with worsening fatigue and bone pain. Nine years before presentation, he was treated with prostatectomy, pelvic radiation, and taxotere followed by one year of luteinizing hormone-releasing hormone (LHRH) agonist. Bony metastases were identified 8 years later, and he was treated with a combination of LHRH agonist, RANK-ligand inhibitor denosumab, antiandrogenic therapy abiraterone and prednisone. Due to refractory disease, he received three cycles of sipuleucel-T, a cell-based cancer immunotherapy, and was enrolled in a phase 1B clinical trial involving enzalutamide. Laboratory evaluation included phosphorus 1.2 (2.5-4.5 mg/dL), urine phosphate excretion 1984 (400-1300 mg/24 hour), parathyroid hormone 110 (15-65pg/mL), calcium7.9 (8.7-10.2 mg/dL), vitamin D-25 85.3 (30-100mg/dL), inappropriately low vitamin D 1,25 40 (19.9-79.3 mg/dL) and FGF-23 387 (44-215 ref units/mL). Whole body scan showed widespread osteoblastic metastatic lesions. He was treated with high-dose calcitriol, vitamin D, calcium carbonate, and potassium phosphate with improvement in hypophosphatemia and bone pain. Clinical Lessons: Hypophosphatemic osteomalacia in the setting of advanced prostate cancer was first reported in 1975. The role of FGF-23 as a phosphatonin in such cases has since emerged, due to advancement of laboratory assays and improved understanding of the pathophysiology of TIO. Review of existing literature reveals five reported cases of prostate cancer-associated TIO with associated elevated FGF-23. This condition poses a diagnostic challenge, as TIO-related bone pain and weakness can be mistaken for that associated with bony metastases. Given the inability to resect widely metastatic disease, treatment of such cases consists of reducing tumor burden with chemotherapy and radiation and supplementation with calcitriol and phosphorus. While other FGF pathways have been implicated in prostate cancer-related angiogenesis, drug resistance, and metastases, the role FGF23 may play in an aggressive disease course warrants further investigation, particularly given it may represent a treatment target.